The nature of future conflict - Connaughton, R. M. (Richard Michael), 1942- (London : Leo Cooper, 1995)
"This is not only a book to be studied by every politician and public servant with responsibility for foreign affairs - and hence the preservation of peace - but a valuable source of reference and inspiration for the student of world politics, humanitarianism and military endeavors. Those in commerce and industry who seek to meet the demands of an increasingly troubled world market, suffering as it does from the consequences of inter- and intra-state conflict, will also find much food for thought."--BOOK JACKET.
1. The Historical Perspective -- 2. A Look to the Future -- 3. Agenda for Peace and Limitations Placed upon National Initiative -- 4. The Breeze of Change -- 5. Principles -- 6. The Command and Control of Coalition Operations -- 7. The Military Technical Revolution -- 8. Points of Conflict -- 9. October, 1993 -- 10. Conclusion -- Annexes 'A' Possible Types of Conflict as Envisaged by the British Government -- Annexes 'B' Question of Equitable Representation and Increase in the Membership of the Security Council -- Annexes 'C' The Ten Most Significant Prospective Advances in US Military Technology.
Includes bibliographical references (pages 227-229) and index.
Keywords: United Nations; Since 1989; War -- Forecasting; World politics -- 1989-; Low-intensity conflicts (Military science); Civil war; Ethnic relations; Intervention (International law); Civil war; Ethnic relations; Wars